Eusebius and the Jewish authors : his citation technique in an apologetic context - Inowlocki, S. (Ancient Judaism and Early Christianity, 2006)
Eusebius and the Jewish Authors examines Eusebius of Caesarea's use of non-biblical Jewish texts (e.g. Philo, Josephus, Aristobulus) in his Praeparatio evangelica and Demonstratio evangelica . In the first part, Sabrina Inowlocki looks at the citation process in Ancient Greek Literature and in Eusebius' own double apologetic work. She also analyzes Eusebius' conception of Judaism. The second part is devoted to a detailed study of Eusebius' methodology in appropriating these texts from both a philological and a philosophical/theological perspective. Through the lens of his exploitation of Jewish quotations, this book defies the traditional perception of Eusebius as being a mere compiler and nuances the manner in which his presentation of the relation between Judaism and Christianity is often seen. This study will be very useful to readers interested in the reception of Jewish texts in Christian literature, in the relations between Judaism and Christianity, and in Christian apologetics. This translation was made possible through a generous grant from the Fondation Universitaire in Brussels (www.fondationuniversitaire.be).